2017
DOI: 10.30535/mto.23.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Tonal Ambiguity in Popular Music’s Axis Progressions

Abstract: The harmonic progression of aFCG (Am–F–C–G) and its transpositions constitute one rotation of what I callAxis progressions, namely progressions that begin with one of these four chords and cycle through the others in order, hence the Axis-a, -F, -C, and -G, respectively. Of these four progressions, the a-form and C-form, and to a lesser extent, the F-form, have become staples of mainstream popular songs from the last decades of the twentieth century and the first decades of the twenty-first. The a-form is espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…[2.15] Another behavior that manifested in our data was pa ern matching, particularly in responses to the four-chord progression in the song "Halo." This progression is very similar to the more common "Axis" four-chord loop shown in Example 14 (Richards 2017), and quite a few participants appeared to make this connection. Several wrote the roman numerals of the Axis progression instead of the correct progression, often adding one of the common names for the progression.…”
Section: ˆˆsupporting
confidence: 59%
“…[2.15] Another behavior that manifested in our data was pa ern matching, particularly in responses to the four-chord progression in the song "Halo." This progression is very similar to the more common "Axis" four-chord loop shown in Example 14 (Richards 2017), and quite a few participants appeared to make this connection. Several wrote the roman numerals of the Axis progression instead of the correct progression, often adding one of the common names for the progression.…”
Section: ˆˆsupporting
confidence: 59%
“…CAmFG is a chord progression commonly associated in pedagogical materials with the doo-wop style, whose peak of popularity was in the late 1950s and early 1960s, and that is still used relatively often today (Doll, 2017; Rosenberg, 2014). CGAmF and AmFCG, have become extremely common in mainstream popular music since the mid-1990s (Anderson et al, 2011; Doll, 2017; Richards, 2017; Rosenberg, 2014). In the specific case of CGAmF and AmFCG, Richards (2017) found that these two chord progressions are included in more than 10% of the 2517 songs that reached the Billboard Year-End Hot Singles charts between the years 1990 and 2016.…”
Section: Methodsmentioning
confidence: 99%
“…CGAmF and AmFCG, have become extremely common in mainstream popular music since the mid-1990s (Anderson et al, 2011; Doll, 2017; Richards, 2017; Rosenberg, 2014). In the specific case of CGAmF and AmFCG, Richards (2017) found that these two chord progressions are included in more than 10% of the 2517 songs that reached the Billboard Year-End Hot Singles charts between the years 1990 and 2016. Additionally, we chose AmCGF because of its relation to Adele’s “Hello” (see Figure 1a).…”
Section: Methodsmentioning
confidence: 99%
“…Notions of commerciality are inherently interwoven with the idea of mainstream popular music, in that it is viewed negatively as highly commercial music raising suspicion that it was created solely out of 1 In some articles, musicologists take these kind of songs as representative examples to discuss new analytical conceptualizations (e.g., Attas, 2015; Spicer, 2017; Forrest, 2017; Adams, 2019; Duinker, 2019). A broad repertoire of Billboard Hot 100 songs is examined by Scholz (2014) and Richards (2017).…”
Section: Starting Pointmentioning
confidence: 99%